2021
DOI: 10.3390/nano11061390
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Nanoemulsions Based on a Dynamic Covalent Surfactant

Abstract: Developing solid-free nanoemulsions with pH responsiveness is desirable in enhanced oil recovery (EOR) applications. Here, we report the synthesis of an interfacial activity controllable surfactant (T−DBA) through dynamic imine bonding between taurine (T) and p-decyloxybenzaldehyde (DBA). Instead of macroemulsions, nanoemulsions can be prepared by using T−DBA as an emulsifier. The dynamic imine bond of T−DBA enables switching between the active and inactive states in response to pH. This switching of interfaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…It was observed that the mean droplet size (152.1 nm) and PDI (0.154) of OA-based NE system was significantly increased in the buffer of acidic pH 1.2 compared to NE system at pH 6.8 ( p < 0.05) ( Figure 4 a). OA-based NE formulation contains a carboxyl group as a pH-responsive group, which upon pH changes resulted in the protonation or deprotonation of the responsive group in the formulation system [ 37 ]. A pKa value of 4.89 of OA indicates that it will exist almost entirely in the anion form at pH values of 5–9 [ 38 ] and get protonated upon a change in pH to acidic pH 1.2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the mean droplet size (152.1 nm) and PDI (0.154) of OA-based NE system was significantly increased in the buffer of acidic pH 1.2 compared to NE system at pH 6.8 ( p < 0.05) ( Figure 4 a). OA-based NE formulation contains a carboxyl group as a pH-responsive group, which upon pH changes resulted in the protonation or deprotonation of the responsive group in the formulation system [ 37 ]. A pKa value of 4.89 of OA indicates that it will exist almost entirely in the anion form at pH values of 5–9 [ 38 ] and get protonated upon a change in pH to acidic pH 1.2.…”
Section: Resultsmentioning
confidence: 99%
“…A pKa value of 4.89 of OA indicates that it will exist almost entirely in the anion form at pH values of 5–9 [ 38 ] and get protonated upon a change in pH to acidic pH 1.2. This switching of the responsive group between deprotonated to protonated state due to the change in pH of the aqueous phase is responsible for contributing to the pH-responsive nature of the NE [ 37 ] and results in an increase in mean droplet size of OA-based NE formulation at pH 1.2. On the contrary, it was observed that the mean droplet size (210.1 nm) of C90-based NE system was significantly larger in a buffer of pH 6.8 compared to the mean droplet size (153.5 nm) of C90-based NE system at pH 1.2 ( p < 0.05) ( Figure 4 b).…”
Section: Resultsmentioning
confidence: 99%
“…A calibrated pH meter (WTW- INO LAB, Switzerland) was used to measure the pH of all prepared formulations by immersing the instrument bulb into 30 mL of each formulation ( Mahtab et al, 2016 , Ren et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thanking the dynamic covalent chemistry (Belowich & Stoddart, 2012), dynamic imine‐based surfactants (DIBS) are pH‐switchable and have attracted extensive attention (Li & Liu, 2022; Liu et al, 2022; Minkenberg et al, 2011; Ren et al, 2021; Wang et al, 2022; Zentner et al, 2019). Unlike traditional pH‐switchable surfactants, DIBS can be “cleaved” reversibly between a surfactant and two precursors (Li & Liu, 2022; Liu et al, 2022; Minkenberg et al, 2011; Ren et al, 2021; Wang et al, 2022; Zentner et al, 2019). The pH‐stimulus is simple to operate and the DIBS is fast to respond.…”
Section: Introductionmentioning
confidence: 99%
“…The pH‐stimulus is simple to operate and the DIBS is fast to respond. The reversible formation of DIBS‐based micelles (Ren et al, 2021), vesicles (Minkenberg et al, 2011), and emulsions (Li & Liu, 2022; Liu et al, 2022; Wang et al, 2022) have been observed under reversible pH tuning. However, most of the DIBS reported so far are ionic in nature; the nonionic DIBS (Zentner et al, 2019) is rarely reported.…”
Section: Introductionmentioning
confidence: 99%